Reduction in Clostridium difficile infection associated with the introduction of hydrogen peroxide vapour automated room disinfection. Issue 2 (October 2016) - McCord, J.; Prewitt, M.; Dyakova, E.; Mookerjee, S.; Otter, J.A.
Summary: The clinical impact of implementing hydrogen peroxide vapour (HPV) disinfection of rooms vacated by patients with Clostridium difficile infection (CDI) was evaluated. Breakpoint time series analysis indicated a significant reduction ( P <0.001) in the CDI rate at the time when HPV disinfection was implemented, resulting in a reduction in the CDI rate from 1.0 to 0.4 cases per 1000 patient-days in the 24 months before HPV usage compared with the first 24 months of HPV usage. HPV should be considered to augment the terminal disinfection of rooms vacated by patients with CDI.